Exploring Modern Islamic Boarding School English Textbooks Based on the SLA Principles - Saputri, Avida Pramayshela (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2025)
The main focus of this study is to analyze the activity in the